2020
DOI: 10.1177/0960327120979032
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PART1 promotes lung squamous cell carcinoma progression via miR-185-5p/Six1 axis

Abstract: Dysregulation of the long non-coding RNA prostate androgen regulated transcript 1 (lncRNA PART1) is involved in the tumorigenesis of various cancers. However, little is known about its function and molecular mechanism in the development of lung squamous cell carcinoma (LSCC). In this study, we examined the expression of PART1 in LSCC clinical tissue samples and cell lines, and gain- and loss-of-function experiments were performed to explore the function of PART1 in LSCC proliferation, invasion and migration. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The investigators found that miR-185-5p attenuated the proliferative capacity of tumor cells, promoted tumor cell apoptosis, and delayed prostate cancer progression by downregulating RNCR3 expression [ 17 ]. Yu et al reported that miR-185-5p was under-expressed in lung squamous cell carcinoma tumor tissues and NSCLC cell lines, and low miR-185-5p expression was an independent risk factor for poor patient prognosis [ 18 ]. Additional studies reported that LncRNA MALAT1 and MDM4 were upregulated in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators found that miR-185-5p attenuated the proliferative capacity of tumor cells, promoted tumor cell apoptosis, and delayed prostate cancer progression by downregulating RNCR3 expression [ 17 ]. Yu et al reported that miR-185-5p was under-expressed in lung squamous cell carcinoma tumor tissues and NSCLC cell lines, and low miR-185-5p expression was an independent risk factor for poor patient prognosis [ 18 ]. Additional studies reported that LncRNA MALAT1 and MDM4 were upregulated in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic value of PART1 has been evaluated in the context of esophageal squamous cell carcinoma ( Kang et al, 2018 ) and lung squamous cell carcinoma ( Cao et al, 2021 ) ( Table 6 ). In the former type of cancer, PART1 levels could differentiate between gefitinib responders and non-responders with AUC value of 0.839 ( Kang et al, 2018 ).…”
Section: Role Of Part1 In Cancersmentioning
confidence: 99%
“…In brief, cells were washed with cold PBS and resuspended in binding buffer and fixed, then incubated for 10 min in the dark with 5 μL Annexin V-FITC and 5 μL 7-AAD staining solution at room temperature. After mixing with 400 μL 1 × binding buffer, apoptosis was examined with FACS Calibur flow cytometer (Bection Dickinson) within 1 h. 18…”
Section: Flow Cytometry Assaymentioning
confidence: 99%